Estratégia alimentar e suplementação com pó de folha de Lippia alba para jundiás - Santos, Letiely Francine Rodrigues dos (2017)
The optimization of nutritional management is a fundamental aspect in fish production, which also consists in the evaluation of metabolic and health aspects of the animals. The objective of this study was to evaluate the use of Lippia alba leaf powder in silver catfish submitted to different feeding strategies. For this, we conducted an experiment lasting 63 days, in which 360 silver catfish (initial average weight = 6,25±3,18 g) were distributed in 18 tanks in a completely randomized experimental design with factorial arrangement (3 x 2). Three feeding strategies (7 days of feeding, 6 days of feeding / 1 day of fasting and 5 days of feeding / 2 days of fasting) were tested, without the inclusion of L. alba leaf powder and with the inclusion of 0,5% . Fish were fed 3% total biomass twice daily (9 and 17 hours). At the end of the experiment, zootechnical parameters were measured and biological material was collected to evaluate hematological, metabolic and oxidative parameters. It was observed that in the different dietary strategies the treatment with 1 day of restriction did not differ significantly from the control treatment (daily feed). There was also a decrease in fat and increase in fish body protein. There was a decrease in growth and impairing in hematological parameters of fish fed with 0.5% of L. alba leaf powder. In animals subjected to dietary restriction, undesirable metabolic alterations occurred, such as increase of glutamic oxalacetic transaminase (OGT) in the plasma, indicating liver damage. Dietary deprivation and the presence of L. alba in the diets resulted in a decrease in lipid peroxidation in the gills, an increase in the liver, where non-protein thiols were also reduced. The 1 day fasting strategy can be used for silver catfishjuveniles. The addition of L. alba leaf powder to the level tested in this study in silver catfish juveniles is not recommended.